THERMAL SIMULATIONS, COMPARE COOLING STRUCTURES FOR ASYNCHRONOUS SERVOMOTOR - Bắc (Journal of Military Science and Technology, 2021)
This paper presents thermal simulations and compares different cooling structures of an asynchronous servomotor. Thank to the advantage of almost instantaneous calculation speed, the design process can quickly analyze the thermal changes in motor components. The Motor-CAD software is used to select parameters related to the heat generation in the optimal design of the electric machine. The application of thermal-electromagnetic simulation in the design process reduces the requirements for prototype manufacturing and testing, thus reducing the research time and costs. Based on the results of thermal analysis and the threshold temperature limit of the components in the machine, this paper has both objectives: considering the optimal parameters and selecting the cooling architecture to minimize the mass or the production cost, while maximizing the peak torque of the servomotor.